Impact of dual sensory impairment on cognition in older Chinese adults: a moderated chain-mediated effect - Mao, Qingyun; Liang, Heting; Yuan, Xiaoli; Jiang, Zhixia; Hu, Rujun; Zhang, Yumeng; Li, Shuang; Yang, Xiaoling (Frontiers in Public Health, 2025)
ObjectiveAlthough sensory impairment has been identified as a risk factor for cognitive decline, little is known about the underlying mechanisms that connect dual sensory impairment to cognitive ability. This research used a moderated chain-mediated model to investigate the underlying mechanisms behind the association between dual sensory impairment and cognitive ability.MethodsPeople aged 60 years and older from seven medical institutions, three communities, and five nursing homes in Zunyi city, Guizhou Province, were selected for the study from October 2022 to September 2023 via convenience sampling. Data on demographic characteristics, self-reported hearing and vision loss, and Self-Rating Anxiety Scale (SAS), 15-item Geriatric Depression Scale (GAD-15), Frailty Scale (FRAIL), and Mini-Mental State Examination (MMSE) scores were collected. A moderated chain mediator was used to analyze the underlying mechanisms and pathways of the relationships among anxiety, depression, and cognitive ability in individuals with dual sensory impairment, as well as the moderating role of frailty in this connection.ResultsA total of 7,021 older adults were included, 3,598 (51.25%) of whom were male, with a mean age of 72.01 ± 7.17 years. Dual sensory impairment had a significant direct effect on cognitive ability, with an effect size of −3.134, followed by anxiety and depression, which not only independently mediated the relationship between dual sensory impairment and cognitive ability but also jointly had a chain mediation effect, with mediation effect sizes of −0.766 and −0.182, respectively, and a chain mediation effect size of −0.257. In addition, the interaction effect of dual sensory impairment and frailty was significantly predictive of cognitive ability (effect value = −0.575, p < 0.001).ConclusionThe mechanisms of action between dual sensory impairment, anxiety, depression, cognitive performance, and frailty are shown in this study. This finding also implies that therapies for psychological issues, frailty, and sensory functioning in older adults can preserve their cognitive ability.